Letter from Eugène Lemercier to his mother, Marguerite Lemercier, describing his life at the second line - Lemercier, Eugène Emmanuel, 1886-1915; Lemercier, Marguerite, 1859-ca. 1930 (1914)
Mentions Mme Capamagian, Pierre and Charles Rapp and his friendship with them; details about the shelter in which they are, they can only lie and go out at night; still doing his night errand and describes what he sees en route; wants to be even closer to his mother in their joint yearning for wisdom.
Addressed to "Madame Lemercier / 40 Rue Lauriston / Paris". No postmark.
Keywords: Lemercier, Eugène Emmanuel, -- 1886-1915 -- Correspondence; World War, 1914-1918 -- France; World War, 1914-1918 -- France -- Correspondence; France -- History -- 1914-1940